Effects of freezing pork chops on warner-bratzler shear force and cookery traits - B S Andrews; John A Unruh; Melvin C Hunt; Curtis L Kastner (Kansas Agricultural Experiment Station Research Reports, 2000)
Eighty-one boneless pork loins were used to determine the influence of freezing and pH on Warner-Bratzler shear force (WBS) values and cookery traits. Chops with lower pH (6.2). Similar to cooking losses, total moisture losses decreased with increased pH. Frozen chops had lower WBS values (more tender) than fresh chops. However, fresh chops had a higher total yield (lower moisture loss) than frozen chops.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Pork; Quality; Freezing